KEPENTINGAN CINA DALAM MEMBANGUN MILITARY SUPPORT HUB DI DJIBOUTI - Kiki Wiyanti Pri Utami; Erna Kurniawati (Jurnal Paradigma, 2017)
State will make various efforts to achieve or protect its national interests. One of its efforts is to build overseas military base like China does. China’s building a military base in Djibouti, which will be its first overseas military base after China has committed not to rent or build overseas military base. Looking at it from the perspective of geostrategic and national interest, this study will explain China’s interests in building a military base in Djibouti. This study will explain two Chinese interests in building the base, namely economic interests and security interests.